Comparison of different FETI preconditioners for elastoplasticity. (1st July 2017) - Čermák, Martin; Hapla, Václav; Kružík, Jakub; Markopoulos, Alexandros; Vašatová, Alena
Abstract: This paper illustrates parallel solution of elastoplastic problems with hardening based on the TFETI domain decomposition method with several preconditioning strategies. We consider von Mises plasticity with isotropic hardening using the return mapping concept for one time step. To treat nonlinearity and nonsmoothness, we use the semismooth Newton method. In each Newton iteration, we solve a linear system of equations using the TFETI domain decomposition method with lumped, Dirichlet, or no preconditioner. Our PERMON software is used for the numerical experiments. The observed times and numbers of iterations are backed up by the regular condition number estimates. Both preconditioners accelerate the solution process in terms of the convergence rate. For the worst conditioned benchmark, the most expensive Dirichlet preconditioner gives the lowest computational times. This lets us suggest the Dirichlet preconditioner as the default choice for engineering problems.